The efforts of town planning system in Wetland Management in Peninsular Malaysia - Asmawi, M. Zainora (KAED, IIUM, 2007)
This paper examines about development plan as one element of town planning system can and should make a substantial contribution to wetland management in Peninsular Malaysia. By practising the development plan system, it is anticipated that the protection and conservation of nation’s valuable wetland will be strengthened. The legislation backup of the town planning system offers a strong support for development plan in ensuring the sustainability of wetland habitats are achievable in the long run. Policy and strategy stated in development plan are the mechanisms of town planning system in relation to contribute to wetland management in Peninsular Malaysia.